The Center for Community Engagement and Faculty: A Collaboration For Making a Better Service Learning Experience - Montano, Isamar; Rocha, Rosalba; Vlahakis, Jessica; Osaah, Beverly; Uy, Harvey; Abell, Leslie (CBR@CSUCI: An annual volume of community-based research, 2019)
The Center for Community Engagement (CCE) is one of four centers that are designed to promote California State University Channel Islands’ mission. Specifically, the CCE provides resources to faculty, community partners, and students who are involved in service learning courses. The CCE is integral to fulfilling the mission since it connects students to the broader community and promotes learning through experience and service. Although most research on service learning focuses on the students’ experience and how students are transformed by their service, much less is devoted to faculty experiences. However, understanding faculty experiences with service learning is vital since faculty are the ones that organize and facilitate these courses on a day-to-day basis. Thus, it is important to recognize what resources faculty use when planning these courses and what constitutes some of the best practices to make service learning successful. This research project seeks to identify, describe, and analyze the best teaching practices of faculty in service learning courses and which resources faculty use in order to create a service learning course at CSUCI. Through our in-depth interviews with 12 faculty who taught service learning courses within the academic year of 2015, we find that faculty are utilizing the suggested best practices but are doing so in individualized ways. These faculty feel overwhelming supported by the CCE but would like to see some sort of faculty support or mentorship group for service learning faculty.